(untitled) (Scientia Agricola, 2011)
Carrizo citrange [Citrus sinensis (L.) Osb. × Poncirus trifoliata (L.) Raf.] and Cleopatra mandarin (C. reshni Hort. ex Tan.) are the most important rootstocks used in Spain, but they are problematic and it is necessary to search for new rootstocks with better all-round performance. The performance of 'Lane Late' navel orange [Citrus sinensis (L.) Osb] on ten rootstocks was determined in the South of the province of Alicante (Spain). They are Carrizo citrange, Cleopatra mandarin and eight new hybrids obtained at the Instituto Valenciano de Investigaciones Agrarias in Valencia (Spain): 020324 [Troyer citrange (C. sinensis × P. trifoliata) × Cleopatra mandarin], Forner-Alcaide 418 (F&A 418) [Troyer citrange × common mandarin (C. deliciosa Ten.)], Forner-Alcaide 13 (F&A 13), 030118, 030127 and 030131 (Cleopatra mandarin × P. trifoliata) and 030212 and 030230 (Cleopatra mandarin × Troyer citrange). Soil is clay loam, with pH 8.5 and electric conductivity in the saturation extract at 25ºC of 5.79 mS cm-1. Yield was weighed during the first nine harvests, fruit quality was determined in the last three. Pre-harvest fruit-drop was controlled for the 4th until 9th harvests. The trees of 'Lane Late' navel budded on Cleopatra mandarin were the tallest (2.5 m) and F&A 418 (1.6 m) the shortest of all rootstocks tested. Trees on 030131 hybrid and Carrizo citrange rootstocks had the highest mean yield (81.2 and 80.3 kg per tree per year respectively), while trees on F&A 418 produced the lowest mean yield (22.3 kg per tree per year). Trees on 030131, 020324 and 030212 had the highest yield efficiency as total cumulative yield per cubic meter of canopy volume (62.1, 58.7 and 55.9 kg m-3 respectively) whereas trees on 030127, F&A 418 and Cleopatra mandarin had lower yield efficiencies (45.0, 44.4 and 38.6 kg m-3, respectively). Pre-harvest fruit-drop was lower in trees grafted on Cleopatra mandarin (24.62 %) and on 030212 (26.61 %), and was also low on F&A 418 (27.76 %), 020324 (28.14 %) and 030230 (29.18 %) rootstocks. Trees on Carrizo citrange and 030127 experienced important fruit-drop (40.24 % and 38.27 % respectively). Trees on F&A 418 had the highest fruit weight and fruit size whereas trees on 030118 induced the lowest ones. The ripeness index was the highest on F&A 13 (18.3) and lowest on F&A 418 (15.3), 030212 (15.3).